Halal supply chain: mediating role of intention on manufacturer’s behaviour to utilize halal transportation services - Ustadi, Muna Norkhairunnisak (2022)
As one of the world's major Muslim countries, Malaysia is seeing a growth in demand for halal products. Muslim consumers think that eating halal food is a religious responsibility for all Muslims. The increased awareness of the importance of halal products creates a sizable market opportunity for producers to make their halal products. In accordance with this, halal transportation services are a critical component of halal product manufacturing. Since halal is distinct and entails intricate regulations and executions, it requires significant expenditure. As with any other supply chain, transportation costs will be passed to end-users, typically customers, increasing the final product's price. While studies on Muslim customers and their preferences for halal products are somewhat widespread, studies on Muslim customers' preferences for halal transportation could still be considered as novel. The purpose of this research is to apply the hybrid theories of TRA and TPB as popular theories due to their relative simplicity and flexibility, as well as their effectiveness in forecasting customer intention and actual behaviour to use halal transportation services. From the 1729 manufacturers initially listed, 130 manufacturers were randomly chosen from the food and beverages operators in the Klang Valley listed on the Jabatan Kemajuan Islam Malaysia (JAKIM) website. 3 sets of questionnaires were distributed to each halal certified manufacturer in this survey to maintain homogeneity among the halal food and beverages manufacturers. A total of 390 people were sent the questionnaires. Foreign multinationals, Malaysian multinationals, Small and Medium Enterprises (SME), and bigger enterprises were the four types of companies that participated in this study. This study was designed to provide a better knowledge of Muslim customers' purchasing behavior regarding Halal transportation and other Halal supply chain operations. Additionally, this study may assist policymakers in forecasting consumer behavior toward Halal transportation and enhance their business strategies through sharia compliance to better serve Muslim consumers.